2018
DOI: 10.1108/rpj-03-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

A study on extruded filament bonding in fused filament fabrication

Abstract: Purpose The performance of parts produced by fused filament fabrication is directly related to the printing conditions and to the rheological phenomena inherent to the process, specifically the bonding between adjacent extruded paths/raster. This paper aims to study the influence of a set of printing conditions and parameters, namely, envelope temperature, extrusion temperature, forced cooling and extrusion rate, on the parts performance. Design/methodology/approach The influence of these parameters is evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
4
37
0
2
Order By: Relevance
“…Two sources of overextrusion can be found in this study: the programmed overextrusion caused by the perimeter-infill overlap and the uncontrolled overextrusion by the changes in the filament diameter. In principle, the overextrusion of material is an effective way to reduce the porosity in FFF parts [ 67 , 68 ]. Nevertheless, an excessive overextrusion leads to a “flooding” of material between roads and structures such as the one shown in Figure 11 a [ 8 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two sources of overextrusion can be found in this study: the programmed overextrusion caused by the perimeter-infill overlap and the uncontrolled overextrusion by the changes in the filament diameter. In principle, the overextrusion of material is an effective way to reduce the porosity in FFF parts [ 67 , 68 ]. Nevertheless, an excessive overextrusion leads to a “flooding” of material between roads and structures such as the one shown in Figure 11 a [ 8 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the overextrusion of material is an effective way to reduce the porosity in FFF parts [ 67 , 68 ]. Nevertheless, an excessive overextrusion leads to a “flooding” of material between roads and structures such as the one shown in Figure 11 a [ 8 , 68 ]. Figure 11 b shows the origin of the overextrusion defects, which can eventually result in the apparition of new types of defects, as shown by Costa et al [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile test specimens were printed with the flat side down and the long axis aligned with the x‐axis of the build platform. This orientation results in the majority of the deposited beads of material aligned parallel to the applied load, which has been shown to maximize the mechanical strength of printed specimens 27‐32 . Solid cylindrical specimens were printed with 8 mm diameters and 10 mm lengths for micro‐CT analysis (Figure 1b,c).…”
Section: Methodsmentioning
confidence: 99%
“…Spoerk et al printed polypropylene (PP) filled with glass spheres, which showed better annealing quality and dimensional accuracy with an elevated chamber temperature [ 17 , 18 ]. Carneiro et al found that a 20 °C increase in environmental temperature reduced the structural porosity of printed acrylonitrile butadiene styrene (ABS) by 50% [ 19 ]. Armillotta et al studied the specimen warpage with both analytical and experimental approaches, and they reported that a high chamber temperature close to the glass transition temperature significantly reduced the warpage [ 20 ].…”
Section: Introductionmentioning
confidence: 99%